Sustainable Choices and Behaviors among Eco-Friendly Museum Travelers: Exploring the Drivers of Sacrifice, Visit, Pay, and WOM Intentions - Heesup Han; Linda Heejung Lho; Hyeon-Cheol Kim; Elena-Nicoleta Untaru (My University, 2021)
This research developed a sturdy theoretical framework that offers a better comprehen sion regarding customer approach intentions for eco-friendly museum products. Using a quan titative process, the apparent role of ecological value, connectedness to nature, social pressure, pro-environmental reputation was explored. Data quality testing demonstrated the validity of the construct measures. The critical mediating nature of customer-product relationship quality and feeling of pride was unveiled by conducting a structural analysis. In addition, the feeling of pride was aprominent factor determining sacrifice, visit, pay, and word of mouth (WOM) intentions. Social pressure played a major role in building relationship quality, whereas pro-environmental reputation was a key contributor to increase the feeling of pride. The model contained a strong prediction power for intentions. Results of this study contribute to enriching the extant knowledge regarding customer pro-environmental decision-making process, which is helpful for an eco-friendly museum and its success.
Keywords: eco-friendly museums; pro-environmental intentions; customer-product relationship quality; feeling of pride; connectedness to nature; social pressure; reputation; ecological value